Husserl and The Problem of Animal - Marosan, Bence Peter (B@belonline, 2020)
The main aim of this paper is to give an overview of Husserl’s attempts to unfold the phenomenon of animal consciousness, and particularly the lowest level of subjectivity. I wanted to show that in this context Husserl’s notion of life is especially important. The phenomenon of life for Husserl was essentially the inner, mental activity of a subject or consciousness. Husserl understood life as a perpetual process of self-normalization; according to him, life normalizes itself on different levels of complexity. The reconstruction of lowest level of subjectivity is at the same time the reconstruction of the lowest level and most rudimentary form of self-normalization of life. Husserl had fundamentally three ways to approach the problem of animal mind: empathy, eidetic variation and dismantling-deconstructive reflection (“Abbau”) on the own subjectivity of the phenomenologist. The first refers to the problem of empathizing with anomalous subjects (such as an animal), and to the question, how wide is the range of empathy, and towards which living beings could we be empathic, in a phenomenologically legitimate way? The second is to grasp the eidetic (essential) structures of consciousness in general, and remove eidetic moments and structures from it, and see which are the most fundamental structures of subjectivity, without which no consciousness could be conceived at all. The third way is the dismantling-deconstructive approach of one’s own consciousness. The subjectivity in general appears as having several main layers, and the phenomenologist abstracts from the higher layer, in order to reach the deepest one. Once the lowest level is disclosed in this way, a subject could be reconstructed who possesses only the most fundamental, simplest structures and elements of subjectivity.